Infância e Sexualidade: pesquisa bibliográfica sobre os impactos da violência sexual na vida escolar e na aprendizagem de crianças vítimas - Mendes, Valéria Lima (Universidade Federal do Tocantins, 2022)
The present course conclusion work has as elements to verify how the theme of the impacts of sexual violence in the school life of child victims is treated in the scientific literature. The general objective of this work was to understand how research addresses the impacts of sexual violence on school life and on the learning of child victims, in scientific publications in academic journals, in course conclusion papers, dissertations and in government documents. bibliographic and documental analysis. We assume as theoretical guidance the contributions of Freud (2002), Ribeiro (2017), Camargo and Ribeiro (1998), Brino and Williams (2008), Amazarray and Koller (1998), Dell'aglio (2008), Rodrigues (2017), Nedeff (2001). The bibliographic research was carried out through the survey of articles, books, theses and